DEPFET pixel detector in the Belle II experiment - Abudinén, Fernando; Ritzert, Michael (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2019)
The Belle II experiment will run with a reduced beam asymmetry and a factor of 40 higher instantaneous luminosity compared to the Belle experiment. To cope with this and to be able to perform high precision vertex measurements for charge conjugation parity violating processes, a pixel detector based on DEPFET technology will be installed in the center of Belle II. Its basic properties and the DAQ chain are presented in this article.
Available onlin 15 October 2018
Gesehen am 09.07.2019